Implementing Sustainability Criteria in Product Development. (2015) - Lacasa, E.; Santolaya, J.L.; Fuentes, L.; Majarena, A.C.
Abstract: This work analyses the product development process of two different mechanical assemblies in order to put into practice redesign strategies that allow obtaining more sustainable products. The study of the manufacturing process has been focused on obtaining material and energy consumptions. Sustainable design criteria have been applied preserving the initial specifications of each product. A number of approaches as the material replacement, the reduction of the final product mass and an effective utilization of raw materials have been proposed. A reduction of the environmental impact, which was assessed trough global energy and global warming eco-indicators, has been achieved.